Do Islamic stock indexes integrated with conventional stock indexes?: Evidence from Indonesia and Malaysia - Rusmita, Sylva Alif; Swastika, Putri (Asian Management and Business Review, 2021)
The portfolios performance that are develop either a substitute or complement in terms of risk-taking is important information for investors whether the return portfolio could hedge the risk of shock market. An understanding of volatility and the correlation between asset returns over time vary is highly important for investors (both domestic and international) with the sight of diversifying their portfolios for hedging from unexpected risk. The research method uses a DCC MGARCH approach to examine the correlation among two countries in time variant manner to indicate the degree of financial integration. With daily data from April 2012 until December 2017 and use 3 category index (composite, Islamic and conventional) the result shows that Malaysia and Indonesia have strong correlation. Among Islamic, composite and conventional have financial integration, but conventional index in Malaysia have the lowest integration from other index that it makes suitable for diversification. Unfortunately, conventional index that contain non halal product was not suitable for investor that sharp pointed into sharia. The shock in Malaysia’s Index will be perform different from historical or previous return. Contrary with Indonesia’s index, the return probably based on the historical. The implication of this research is we found that the Islamic investor could not have best diversification on the Malaysia and Indonesia market, since the Islamic index was sturdily correlated.